If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8t+2=3t+12
We simplify the equation to the form, which is simple to understand
8t+2=3t+12
We move all terms containing t to the left and all other terms to the right.
+8t-3t=+12-2
We simplify left and right side of the equation.
+5t=+10
We divide both sides of the equation by 5 to get t.
t=2
| 6.5=2x+3 | | 5+2x=5x-3(x-1)+2 | | x+(x-7)=67 | | 6x^3+x^2-35x=0 | | 5x-2=11x+5-6x | | 21x-4=18x+10 | | 66-3x=6-9 | | 6x-18=9x+6 | | 5x+4=(-1) | | (2sinx+1)(cosx-1)=0 | | 7p-2=p+12 | | 20a-16=12(3-a) | | z^2-(4+i)z+5+5i=0 | | 20a-16=12(3-a)thenais | | X+2X+2X+5=50 | | graphf(x)=24x^2-44+16 | | (13x+3)(9x+1)=180 | | 2(y-4)=16 | | 2m-4+3m=7m-12 | | 2.5x+5=0 | | 6cos^2x=0 | | 2(y-4)=26 | | 3z(z+4)=0 | | f(x)=24x^2-44+16 | | f(x)=18x^2+33-30 | | 6d+7e+11d+11e= | | 15c-11c= | | 0.75y-2.5=0.5y | | 2x-3=10x+4 | | 5(p-7)-2(3-p-4)=3p | | ln(x^8)=7 | | 3*(2x-7)-(3x+3)=4*(5-2x) |